2017
DOI: 10.1016/j.bbamcr.2017.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of RNA molecules by connexin RNA-binding motifs: Implication in RNA and DNA transport through microvesicles and exosomes

Abstract: Connexins (Cxs) are integral membrane proteins that form high-conductance plasma membrane channels, allowing communication from cell to cell (via gap junctions) and from cells to the extracellular environment (via hemichannels). Initially described for their role in joining excitable cells (nerve and muscle), gap junctions (GJs) are found between virtually all cells in solid tissues and are essential for functional coordination by enabling the direct transfer of small signalling molecules, metabolites, ions, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 113 publications
0
42
0
Order By: Relevance
“…More recently, it has been shown that connexins exert cell functions which are independent of their channel forming properties. 11,[105][106][107][108][109][110] By virtue of their interaction with other proteins, they are able to control signalling cascades regulating, for example cell migration, proliferation and growth.…”
Section: Channel-independent Functionsmentioning
confidence: 99%
“…More recently, it has been shown that connexins exert cell functions which are independent of their channel forming properties. 11,[105][106][107][108][109][110] By virtue of their interaction with other proteins, they are able to control signalling cascades regulating, for example cell migration, proliferation and growth.…”
Section: Channel-independent Functionsmentioning
confidence: 99%
“…Polymeric nanocapsules (NCs) are a promising system of natural carriers for targeted drug delivery because of their low cytotoxicity, shell flexibility, and high in vivo stability [22][23][24][25][26]. A wide range of drugs [27][28][29] and nucleotides of ribonucleic acid (RNA)/deoxyribonucleic acid (DNA) [30][31][32] can be effectively encapsulated in the polymer capsules. Effective distribution of drugs in target tissues can be achieved by active delivery methods that are potentially much more beneficial than passive accumulation.…”
Section: Introductionmentioning
confidence: 99%
“…RBP also account for localization and trafficking of RNA-protein complexes in cells (115,116). Finally, the mRNA profile of Exo differs from that of cells (117), metabolic enzymes and proteins engaged in cell-cell and cell-matrix adhesion being frequently overrepresented (118)(119)(120), and possibly translated in Exo (121,122).…”
Section: Exosome Compositionmentioning
confidence: 99%